IMAM AL-BUKHARI DAN LAFAL AL-QUR’AN - Mujib Abdurrahman (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
Imam Abu Abdullah Muhammad ibn Ismail al-Bukhari is the author of the hadith book: al-Jâmi’ al-Shahîh, which is collecting the hadiths of Prophet Muhammad (peace be upon him) and agreed by all Islamic scholars from its day to the present as the most valid and authentic reference book of the Muslims after al-Qur’an. Despite the prestigious position of the book and its author, al-Bukhari apparently got a big test and slanderahead his death. This was because of his thought of Qur’anic words. Al-Bukhari actually just said that word (reading) of al-Qur’an is including human actions, and human being and his deeds are created by God. This word was then concluded logically that Al-Bukhari stated al-Quran readings is creature by God. Sunni scholars, broadly divided into two schools of thought in questioning al-Quran words. Imam Ahmad, experts at hadith and the Hanabilah equated it’s verdict with the opinion of the Qur’an is creature. Meanwhile, al-Bukhari, Thabari, the sunni theologist, and some experts at hadis linked it with af’âlu al-’ibâd.